2002
DOI: 10.1063/1.1432118
|View full text |Cite
|
Sign up to set email alerts
|

n + - GaN formed by Si implantation into p-GaN

Abstract: Si ϩ implantation into Mg-doped GaN, followed by thermal annealing in N 2 was performed to achieve n ϩ -GaN layers. Multiple implantation was used to form a uniform Si implanted region. It was found that the carrier concentration of the films changed from 3ϫ10 17 cm Ϫ3 ͑p-type͒ to 5 ϫ10 19 cm Ϫ3 ͑n-type͒ when the samples were annealed in N 2 ambient at 1000°C. The activation efficiency of Si in Mg-doped GaN was as high as 27%. In addition, planar GaN n ϩ -p junctions formed by Si-implanted GaN:Mg were also ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Details of the growth conditions can be found elsewhere. [9][10][11][12][13][14][15][16][17] The InGaN/GaN MQW LED structure consists of a 30-nm-thick, GaN-nucleation layer grown at a low temperature of 560°C; a 4-mthick, Si-doped, n-GaN-cladding layer; an InGaN/ GaN MQW active region; a 50-nm-thick, Mg-doped, p-Al 0.15 Ga 0.85 N-cladding layer; and a 0.25-m-thick, Mg-doped, p-contact layer. The InGaN/GaN MQW active region consists of five pairs of 3-nm-thick, In 0.05 Ga 0.95 N-well layers and 12-nm-thick, GaNbarrier layers.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the growth conditions can be found elsewhere. [9][10][11][12][13][14][15][16][17] The InGaN/GaN MQW LED structure consists of a 30-nm-thick, GaN-nucleation layer grown at a low temperature of 560°C; a 4-mthick, Si-doped, n-GaN-cladding layer; an InGaN/ GaN MQW active region; a 50-nm-thick, Mg-doped, p-Al 0.15 Ga 0.85 N-cladding layer; and a 0.25-m-thick, Mg-doped, p-contact layer. The InGaN/GaN MQW active region consists of five pairs of 3-nm-thick, In 0.05 Ga 0.95 N-well layers and 12-nm-thick, GaNbarrier layers.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Briefly, trimethylaluminum, trimethylgallium, trimethylindium, and ammonia were used as aluminum, gallium, indium, and nitrogen sources, respectively. Biscyclopentadienyl magnesium (CP 2 Mg) and disilane (Si 2 H 6 ) were used as the p-type and n-type doping sources, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, very limited studies have been made on combined behaviour of Si implantation into Mg-doped p-type GaN as it is used in a GaN MOS-FET device. Electrical characterization of 0.6-µm-deep Si implantation was done by Sheu et al, who showed 27% of activation at 1000 °C [3]. Diffusion of Si in p-type GaN during annealing was studied by Pan et al [4].…”
mentioning
confidence: 99%